Financial Management of Yogyakarta Students: The Role of Locus of Control, Love of Money, and Financial Inclusion - Kumalasari, Anika; Resmi, Siti; Utami, Alivia Meyrizka (JURNAL ILMU MANAJEMEN, 2025)
Financial behavior has always been an interesting topic, especially student financial management. This study examines the role of locus of control, love of money, and financial inclusion variables on financial management carried out by students in Yogyakarta. Data were collected from online questionnaires completed by 120 respondents who met the research criteria. The multiple linear regression analysis results showed that Love of Money and Financial Inclusion positively affected financial management. This shows that Yogyakarta students have an interest in money, and easy access to financial services makes their financial management better. However, Locus of Control did not show a significant effect on financial management. These results indicate that confidence in the results obtained, depending on individual behavior, has not affected students' financial management in Yogyakarta. This study only involved students from several universities in Yogyakarta, so it is impossible to generalize to all students in Yogyakarta. Furthermore, the characteristics of students who are respondents to the study, such as majors, year of enrollment, socio-economic background, and others, can also affect the results of the study. Therefore, this study is expected to add new insights to research related to management behavior.